COMPARATIVE LITERATURE IN INDONESIAN FOLKTALE’S TIMUN MAS AND DISNEY’S BEAUTY AND THE BEAST - Ima Masofa; Irwan Sumarsono (Lingua Scientia, 2021)
Abstract This study is a comparative literature that focuses on the differences of two literary works, namely Timun Mas and Beauty and the Beast. The study analyses the similarities and differences in two different cultures; Asian and Western cultures, by using American School theory. This research usesa qualitative method which was based on library research. The results of this study can be formulated as follows: 1) Both have similarities in facing the monster. (2) Both have differences in the way how the monster is described, and how the stories end; in Timun Mas, the monster is a green huge male, and in Beauty and The Beast, the monster is described as a huge animal. In Timun Mas, the story ends when the main character kills the monster, while in Beauty and The Beast, the main character marries to the monster. Keywords : Comparative Literature, monster, American School